An evaluation of the genus Cyne (Loranthaceae) including a new species and rediscovery and neotypification of the rare C. quadriangula - Nickrent, Daniel L.; Rule, Mark Gregory Q. (Phytotaxa, 2022)
A new species of Cyne (Loranthaceae) from Bucas Grande and Dinagat Islands, Philippines is described and named C. barcelonae in honor of the Filipina botanist Julie F. Barcelona. Phylogenetic analysis using the complete nuclear ribosomal DNA cistron confirms it is sister to C. banahaensis, the only species among the six in the genus with complete descriptions of floral morphology. The species is similar to the rare C. perfoliata of Papua New Guinea by having connate-perfoliate upper leaves but differs from others in the genus by possessing palmate leaf venation, inflorescences lacking an operculum, light green corollas, and stamens with filaments. No type material for Cyne quadriangula exists, thus this taxon is only known from the original protologue. It was rediscovered on Bucas Grande Island and that collection was described and used as the neotype for the species. A revised description of the genus and key to the seven species is provided.